COFFEE COMMUNITY CENTER DI KABUPATEN KUBU RAYA - Prasanti, Maria Garini Dara; Gultom, Bontor Jumaylinda BR; Khaliesh, Hamdil (JMARS: Jurnal Mosaik Arsitektur, 2024)
The society of Kubu Raya Regency has also begun to enjoy drinking coffee, which is shown by the opening of cafÃ© franchises. In addition, Kubu Raya Regency is the largest coffee producer in West Kalimantan, which produces coffee with a unique flavor. This potential can be beneficial, however the coffee industry condition tends to be slow in progress. The aim of this project is to design facilities for the coffee community and non-coffee community with a climate-responsive design and use of natural elements as natural circulation and natural lighting. The method used in this project consists of, analysis and synthesis techniques. This project is located at Jalan Arteri Supadio, Sungai Raya District, Kubu Raya Regency, West Kalimantan. The theme is "Kubu Raya Coffee Communtiy Journey" by forming a coffee community through commercial and educational facilities. Based on educational activities, there are coffee information rooms, personal coffee labs, roasting areas and private coffee classes. The main shape of the building is square with the curved linear circulation, resulting a void that provides natural air and natural lighting. The void area also uses as a coffee garden with a sitting area. The roof is inspired by the Kubu Raya Menanjak logo therefore the roof forms letter "M". The materials used are red bricks, unfinished concrete and steel.